2000
DOI: 10.1002/(sici)1099-1328(200004)12:3<343::aid-jid639>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Productivity spillovers from technology transfer to Indian manufacturing firms

Abstract: The present paper employs techniques from stochastic production frontier and panel data literature to test a spillover hypothesis for large sized ®rms that`presence of foreign-owned ®rms and foreign technical capital stock in a sector leads to reduced dispersion in eciency in the sector and fall is higher for the ®rms that invest in R&D activities'. Dispersion being a relative concept, it may still fall if both the leading foreign ®rm and domestic ®rms show fall in technical eciency over the period and the fal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
107
0
6

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(129 citation statements)
references
References 27 publications
7
107
0
6
Order By: Relevance
“…The first group of empirical studies used cross-sectional data in a single year and found positive spillovers (Caves, 1974;Globerman, 1979;Blomström and Person, 1983;Blomström and Wolff, 1994;Nadiri, 1991;Blomström and Sjöoholm, 1998). But the set of second group of studies, which used panel data, found negative spillovers (Aitken and Harrison, 1999;Djankov and Hoeckman, 2000;Kathuria, 2000;Konings, 2000). The findings pointed out that many of the earlier studies, that found positive spillovers, did not introduce control variables of sectoral nature.…”
Section: Empirical Studies On Spilloversmentioning
confidence: 96%
“…The first group of empirical studies used cross-sectional data in a single year and found positive spillovers (Caves, 1974;Globerman, 1979;Blomström and Person, 1983;Blomström and Wolff, 1994;Nadiri, 1991;Blomström and Sjöoholm, 1998). But the set of second group of studies, which used panel data, found negative spillovers (Aitken and Harrison, 1999;Djankov and Hoeckman, 2000;Kathuria, 2000;Konings, 2000). The findings pointed out that many of the earlier studies, that found positive spillovers, did not introduce control variables of sectoral nature.…”
Section: Empirical Studies On Spilloversmentioning
confidence: 96%
“…On the other hand, they can also have a crowding-out effect on the domestic-owned firms which are not able to meet the competitive arrangements that foreign-owned firms impose on the market, that is, horizontal spillovers. Negative effects can occur in two ways (Aitken, Harrison et al 1996;Aitken, Hanson et al 1997;Aitken and Harrison 1999;Kokko 1994;Kathuria 2000): 1) foreign-owned firms can appropriate the domestic market; or foreignowned firms attract the finest human capital, thus starving the local economy of good quality resources. The literature notes that these negative effects are usually conditioned on several factors in different parts of the world (Blomström and Sjöholm 1999;Konings 2001;Gorodnichenko 2007).…”
Section: Inter-industry Effectsmentioning
confidence: 99%
“…Djankov e Hoekman (2000) e Kathuria (2000) encontram efeitos negativos da presença de multinacionais sobre as firmas domésticas, usando dados de painel para as indústrias da República Tcheca e Índia, respectivamente. Por outro lado, outros trabalhos, como Driffield (2000) e Liu et al (2000), ambos para indústrias do Reino Unido, detectam resultados positivos.…”
Section: Interlúdio Conceitual E Empíricounclassified